Results from Brazil S 2022 Report Card on Physical Activity for Children and Adolescents - De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
This research aims to summarize the process and results of the 2022 Report Card on Physical Activity for Brazilian children and adolescents. A group of experts led by 10 PhD researchers gathered the best possible evidence on physical activity indicators. The Report Card Brazil 2022 included the top 10 indicators of physical activity and sleep, obesity, and poor mental health variables, which made up four dimensions: (I) Daily Behaviors; (II) Settings and Sources of Influence; (III) Government Strategies and Investments; and (IV) Health Outcomes. Comprehensive searches, including peer-reviewed and gray literature searches, were performed for each indicator. Data were considered from systematic reviews, local and national surveys, websites, and official information from the Brazilian Federal Government. Grades from the indicators ranged from F (Active Play) to B (School). In addition, the results found for each indicator were Overall Physical Activity (D), Organized Sport Participation (C−), Active Transportation (C), Sedentary Behaviors (D), Sleep (C), Family and Peers (C−), Community and Environment (C), Government (D+), Physical Fitness (D+), Obesity (11.7%), and Poor Mental Health (37.8%). Successfully strategies for increasing physical activity among Brazilian children and adolescents should look at the different indicators presented in this report. © 2022 by the authors.